The Persian empire from Cyrus II to Artaxerxes I - Brosius, Maria; Brosius, Maria (LACTOR sourcebooks in ancient history ;, 2023)
This volume in the 'LACTOR Sourcebooks in Ancient History' series offers a generous selection of texts on the Persian Empire from Cyrus II to Artaxerxes I (c.600-424 BC), with accompanying map, illustrations, glossary and introductory notes giving crucial background information. It provides for the needs of students at schools and universities who are studying ancient history in English translation and has been written and reviewed by experienced teachers